Study on perception of Omicron, attitude, and acceptance of COVID-19 vaccine among first year MBBS students in a medical college of Assam - Rabha, Alpana Priya; Deka, Upama (International Journal Of Community Medicine And Public Health, 2024)
Background: The SARS-CoV-2 new variant B.1.1529 known as a variant of concern (VOC) has become global concern since detected in 26th November 2021. Effective and safe COVID-19 vaccines have been approved for use since the end of 2020 and countries are actively vaccinated the different age group especially HCWs and other risk population. The present studies have been initiated to know the perceptions on new variant Omicron, knowledge and attitudes of COVID-19 vaccine and its acceptance among the first-year medical students in a tertiary care teaching hospital in a district of Assam. Methods: An institutional based cross-sectional study was conducted among first year medical students from April to June, 2022 at FAAMCH, in Barpeta of Assam. By convenience sampling technique 116 students were participated and data were collected using self-administered structured questionnaires regarding perception of SARS-CoV2 new variant Omicron, their knowledge and attitudes and acceptance on COVID-19 vaccination. Data were analysed in SPSS-16 version. Results: Among the study participants 95.68% were aware of new variant omicron, 29% were on diagnostic test, 94.83% on mode of transmission and 100% on precautionary measures. 100% study participants were aware on COVID-19 vaccine and 97% have taken two doses of COVID-19 vaccines. Conclusions: The study showed that the 111 (95.68%) study participants were aware about new variant Omicron. The level of knowledge on COVID-19 vaccine was 78 (67.24%) average, attitude and acceptance level was 103 (88.79%) found to be higher among the study participants.